The Effectiveness Of Using Information And Communication Technologies In Teaching Geography - Nilufar Urinova (Euro Asian Journal Publishing, 2024)
This article explores the use of Information and Communication Technologies (ICT) in teaching geography. It highlights the advantages of integrating ICT into the educational process, including enhanced student engagement, improved data visualization, and the development of practical skills. Tools such as Geographic Information Systems (GIS), virtual field trips, digital maps, and learning platforms are examined. The study discusses methods for implementing ICT, its impact on the learning process, and challenges related to technology accessibility and teacher training. The findings emphasize the significant potential of ICT in modernizing geography education and fostering critical thinking among students.
Keywords: Information and Communication Technologies; geography; educational platforms